"Selfie-Less" Leadership Development and Self-Reflection. - NEWMAN, DOUGLAS (Public Management (00333611), 2025)
The article focuses on the rise of performative, image-driven leadership in today's social media era and advocates for a return to authentic, selfless leadership grounded in historical perspective. Topics include the dangers of "selfie leadership," the importance of self-awareness through reflection and humility, and how immersive historical experiences like the Gettysburg Leadership Institute can foster meaningful leadership development.